Avaliações em larga escala – Prova Brasil e Prova ANA: Análise das relações com a BNCC 2014-2019 - Maier, Thays Trindade (2020)
The present dissertation developed in association with the Graduate Program in Education from Western Paraná State University - UNIOESTE, Cascavel campus, has as its object of analysis two large-scale evaluations – Prova Brasil and Prova ANA and aims to analyze the relationship between the assessment policy and the development of the Base Nacional Comum Curricular - BNCC (National Common Base for Curriculum) as components of the policies of the evaluating State. The results of largescale evaluations for Elementary Education – Avaliação Nacional de Alfabetização and Prova Brasil (National Literacy Assessment and Prova Brasil) partly comprise the Índice de Desenvolvimento da Educação Básica – IDEB (Basic Education Development Index). Therefore, the assessments and the IDEB are used with the pretext of verifying the quality of teaching and classifying schools based on the results presented by each educational institution. The development of the dissertation was based on documentary research. The theoretical background used considers the multiple determinations for apprehending the historical movement of document production, as the premise that these have a close relationship with the historical, political, and economic period. As a result, it was found that coated in a “new” paradigm, BNCC translates the modernization necessary for survival in the modern world of the 21st century. The explicit concept here refers to an education that reinforces the human formation process desired in the current form of capital sociability, with a certain format, based on large-scale assessments, corroborating with the process of structural adjustment of capital that imposes the need of an evaluating State.